The Effect of an Educational Program on Nurses' Knowledge about Hepatitis B Virus (HBV) in Ninavah Covernorate Hospitals - Mohammed Mohammed Mustafa Wahab; Taha Hassan Taha (College of Nursing,University of Mosul, 2016)
Background and aims: Hepatitis B virus (HBV) considered an infectious disease that affects the liver and is transmitted by blood and body fluids. It still poses a great threat for patients. Nurses are more likely to infected the disease due to dealing with these disease. The purpose of this study is to assess the effect of an educational program on nurses knowledge about HBV and determine relationship between nurses knowledge and demographic characteristics ( gender, age, educational level, years of employment, place of work). Materials and method: A Quasi - experimental study from 28th October 2013 to 31st December 2014. The study sample was randomly selected consisting of (60) nurses from both hospitals, and the sample was divided into two equal groups, the study group (30) nurses in Tal Afar General Hospital and the control group (30) nurses in Ibn Sina Teaching Hospital. To assess and analyze the results of the study, a statistical package for the social sciences(SPSS) program was used through the application of descriptive statistics and inferential statistics. Results: The results of the study showed that the effect of educational program regarding nurses' knowledge toward HBV is positive, The results also showed the differences of statistically highly significant differences in the knowledge of nurses after implementation of the educational program about HBV compared to their knowledge in the period preceding the implementation of the program in study group. The study showed that there is no significant correlation between knowledge about HBV among nurses and some of the demographic characteristics. Conclusion: the presence of a lack in the knowledge of nurses about HBV before application educational program and after applying it, there were improvement. Recommendations: The study recommended to activating continuing nursing education unit or medical education as well as setting points and grades for these actions and calculating the promotion and annual increment as an equivalent point. keywords: Educational program, Hepatitis B, Knowledge and Nurses.